Parâmetros de estresse oxidativo no sangue, fígado e rins de ratos diabéticos tratados com curcumina e/ou insulina - Palma, Heloisa Einloft (2013)
Diabetes mellitus (DM) is an important health problem that affects worldwide human population and is commonly observed in small animal clinics. Many studies show that hyperglycemia is the pivotal cause of DM complications, including cataract, nephropathy and neuropathy. Hyperglycemia leads to generation of reactive oxygen species (ROS) and increases oxidative damage of lipids, DNA and proteins in many tissues. Oxidative stress is increased in cells in response to a depletion of antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT) that scavenge oxygen reactive species. Curcumin is the main component of Curcuma longa and has been used traditionally as an antidiabetic agent; and there are evidences that this substance presents high activity of ROS scavenger. Considering that diet is part of diabetic state treatment and that curcumin is considered and antioxidant agent, this study aimed to evaluate the effects of curcumin and/or insulin on oxidative stress parameters in streptozotocin-induced diabetic rats. In addition, it was performed a histopathological analysis of the liver and kidney of healthy and diabetic rats treated with these compounds. For this, the animals were divided into six groups, with six animals each: Control (C); Control/Curcumin (CCur); Diabetic/Saline (D); Diabetic/Insulin (DIns); Diabetic/Curcumin (DCur), and Diabetic/Insulin/Curcumin (DInsCur). Curcumin was diluted in corn oil and administered at the dosage of 60mg/kg once a day and insulin was administered twice a day, at the dosage of 1.5IU/rat in the morning and 2.5IU/rat in the afternoon, for a period of 30 days. In groups D and DCur, the histological analysis of the liver revealed elevated number of binucleated hepatocytes and alterations in hepatic trabeculae. In kidney there were vacuolization of tubular cells, glomerular congestion and mononuclear inflammatory focus. The treatment with insulin ameliorate renal and hepatic lesions from both DIns and DInsCur groups. Thiobarbituric acid reactive substances (TBARS) levels were increased in serum of D and DInsCur groups and in hepatic and renal tissue of group D (P<0.05). CAT activity was low in liver and kidney of groups D, DIns and DCur; there was significant increase in kidney of DInsCur group; in blood, catalase activity was high in groups D and DInsCur (P<0.05). SOD activity in blood was decreased in groups D and DInsCur and increased in groups DIns and DCur (P<0.05). In liver, SOD activity was increased in groups D and DInsCur. Delta aminolevulinic acid dehydratase (δ-ALA-D) activity was reduced in liver and kidney of group D and treatment with insulin and/or curcumin prevented the decrease of the activity in hepatic tissue from groups DIns, DInsCur and DCur, and renal tissue from groups DCur and DInsCur. Thus, treatments with curcumin or insulin prevented oxidative stress in blood of diabetic rats, through modulation of antioxidant defenses. Regarding lipid peroxidation, both substances presented positive effect in serum, liver and kidney, except in serum from group DInsCur, revealing a negative effect when curcumin and insulin were associated. With this experiment, it was possible to demonstrate the importance of insulin as primary treatment of DM, once this drug prevented cell damage in organs analyzed by histopathology. Furthermore, this study contributed to comprehend that antioxidants from medicinal plants, such as curcumin, can be used as adjuvant in treatment of this endocrinopathy and not as a single therapy.